Epidemiology of the colonization and acquisition of methicillin-resistant staphylococci and vancomycin-resistant enterococci in dogs hospitalized in a clinic veterinary hospital in Spain - Ortiz Díez, Gustavo; López, Raúl; Sánchez Díaz, Ana María; Turrientes López, María Carmen; Baquero Artigao, María Rosario; Luque Mengíbar, Ruth; Maroto, Alba; Fernández, Cristina; Ayllon Santiago, Tania (My University, 2020)
Antibiotic resistance is one of the biggest threats to human and animal health. Methicillin-resistant Staphylococcus spp. (MRS) and vancomycin-resistant Enterococcus spp. (VRE) are of increasing importance in hospital and/or nosocomial infections and represent a potential risk of transmission to humans from infected or colonized companion animals. Studies on the risk factors associated with colonization by multiresistant bacteria in animals are scarce. The present study aimed to estimate the prevalence and incidence of MRS and VRE in canine patients hospitalized in a veterinary hospital and to identify the risk factors for its acquisition and per- sistence. Nasal and perianal swabs were obtained from 72 dogs. Antimicrobial susceptibility assays and molecular detection of mecA and van genes were performed. A prevalence of 13.9% and incidence of 26.5% was observed in dogs colonized by MRS at hospital admission and release, respectively, higher values than those described in most veterinary studies. Thirty-five Staphylococcus isolates had mecA gene and showed higher resistance levels to most of the antimicrobials eval- uated. Previous and concomitant use of antibiotics and corticosteroids has been associated with an increase in MRS colonization. The use of antibiotics in other animals living with the canine patients has also been identified as an associated factor, suggesting cross transmission. The presence of van-resistant genes from Enterococcus spp. was not detected. Pets should be considered possible vehicles of transmission and reservoirs for MRS bacteria and veterinary hospitals should be considered high-risk environments for the occurrence and spread of nosocomial infections and resistant bacteria.
Keywords: Veterinaria; Perros